\(\frac{x}{\sqrt{x}-1}+\frac{2x-\sqrt{x}}{\sqrt{x}-x}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

17 tháng 5 2017

Đặt \(\sqrt{x}=a\)

Khi đó M=\(\frac{a^2}{a-1}+\frac{2a^2-a}{a-a^2}\)( ĐKXĐ : a \(\ne1,a\ne0\))

=> M = \(\frac{a^2}{a-1}+\frac{a\left(2a-1\right)}{a\left(1-a\right)}\)\(\frac{a^2}{a-1}+\frac{2a-1}{1-a}=\frac{a^2}{a-1}+\frac{1-2a}{a-1}\)

          = \(\frac{a^2-2a+1}{a-1}\)=\(\frac{\left(a-1\right)^2}{a-1}=a-1\)\(\sqrt{x}-1\)

Vậy M = \(\sqrt{x}-1\)

17 tháng 5 2017

M = \(\frac{x\sqrt{x}}{\sqrt{x}\left(\sqrt{x}-1\right)}\)  + \(\frac{2x-\sqrt{x}}{\sqrt{x}\left(\sqrt{x}-1\right)}\)

M = \(2\sqrt{x}-1\)

3 tháng 6 2019

ĐK:x>1

M=\(\frac{x-1}{2x}\) .\(\frac{\left(x-\sqrt{x}\right)\left(\sqrt{x}-1\right)-\left(x+\sqrt{x}\right)\left(\sqrt{x}+1\right)}{x-1}\)

=\(\frac{x-1}{2x}\).\(\frac{x\sqrt{x}-x-x+\sqrt{x}-x\sqrt{x}-x-x-\sqrt{x}}{x-1}\)=\(\frac{x-1}{2x}\).\(\frac{-4x}{x-1}\)=-2

Vậy M=-2

31 tháng 3 2020

ĐK \(x>0;x\ne1\)

\(A=\)như trên

\(\Rightarrow A=\frac{x}{\sqrt{x}-1}-\frac{\sqrt{x}\left(2\sqrt{x}-1\right)}{\sqrt{x}\left(\sqrt{x}-1\right)}=\frac{x}{\sqrt{x}-1}-\frac{2\sqrt{x}-1}{\sqrt{x}-1}=\frac{x-2\sqrt{x}+1}{\sqrt{x}-1}=\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}-1}\)

\(\sqrt{x}-1\)

23 tháng 5 2021

\(\frac{4+\sqrt{X}}{7}\)

30 tháng 6 2020

tks